Associations of marrow fat fraction with MR imaging based trabecular bone microarchitecture in first-time diagnosed type 1 diabetes mellitus - Li, Wei; Wang, Wei; Zhang, Minlan; Chen, Qi; Li, Shaojun (Frontiers in Endocrinology, 2024)
Purpose: To determine whether there are alterations in marrow fat content in individuals firsttime diagnosed with type 1 diabetes mellitus (T1DM) and to explore the associations between marrow fat fraction and MRI-based findings in trabecular bone microarchitecture.A case-control study was conducted, involving adults with first-time diagnosed T1DM (n=35) and age-and sex-matched healthy adults (n=46). Dual-energy X-ray absorptiometry and 3 Tesla-MRI of the proximal tibia were performed to assess trabecular microarchitecture and vertebral marrow fat fraction. Multiple linear regression analysis was used to test the associations of marrow fat fraction with trabecular microarchitecture and bone density while adjusting for potential confounding factors.In individuals first-time diagnosed with T1DM, the marrow fat fraction was significantly higher (p < 0.001) compared to healthy controls. T1DM patients also exhibited higher trabecular separation [median (IQR): 2.19 (1.70, 2.68) vs 1.81 (1.62, 2.10), p < 0.001], lower trabecular volume [0.45 (0.30, 0.56) vs 0.53 (0.38, 0.60), p = 0.013], and lower trabecular number [0.37 (0.26, 0.44) vs 0.41 (0.32, 0.47), p = 0.020] compared to controls. However, bone density was similar between the two groups (p = 0.815). In individuals with T1DM, there was an inverse association between marrow fat fraction and trabecular volume (r = -0.69, p < 0.001) as well as trabecular number (r = -0.55, p < 0.001), and a positive association with trabecular separation (r = 0.75, p < 0.001). Marrow fat fraction was independently associated with total trabecular volume (standardized β = -0.21), trabecular number (β = -0.12), and trabecular separation (β = 0.57) of the proximal tibia after adjusting for various factors including age, gender, body mass index, physical activity, smoking status, alcohol consumption, blood glucose, plasma glycated hemoglobin, lipid profile, and bone turnover biomarkers.: Individuals first-time diagnosed with T1DM experience expansion of marrow adiposity, and elevated marrow fat content is associated with MRI-based trabecular Deleted: newly